Micro‐Scale Ice Shoveling Effect Induced by Magnetic‐Responsive Microfins - Yiyi Chen; Ming Liu; Lijing Zhou; Jian Deng; Xianghui Hou; Xuerui Mao (Advanced Science)
Abstract Icing is ubiquitous in nature and engineering applications, and imposes threats to road and air transportations, wind energy infrastructures, etc. However, current active de‐icing solutions, especially the most popular one, i.e., heating, suffer from high energy consumption whilst passive methods are often ineffective at high‐speed, long‐term, or large‐particle conditions. Herein, a promising strategy adopting magnetic‐responsive microfins (MRS) featuring reversible deformations is developed for de‐icing. A novel micro‐scale ice shoveling effect induced by the localized destruction of the ice adhesion interface owing to the inhomogeneous deformation is demonstrated, and its dependence on the ice particle size and temperature is investigated. An analytical model is proposed to describe the mechanism of this effect, showing a linear relation between the position of the magnet and the induced force agreeing well with experiments, leading to a system straightforward to predict and control. Specifically, the de‐icing capacity of the surface becomes prominent when small‐scale ice particles merge to large ones, providing a promising solution for applications on aircraft, wind turbines, etc., as the first of its kind to remove large particles under high‐speed conditions effectively.